Handbook of personal wealth management - "Reuvid, Jonathan.( ed.)" (London, 2006)
This important guide, now fully updated for a second edition and once again endorsed by the Institute of Directors, has been written for high earners and wealthy individuals who are looking to maximise returns on their capital and protect their accumulated wealth. It offers authoritative and jargon-free advice to how to structure personal and business-related finances, as well as providing an accessible overview of current financial products. It includes details on strategies for sound wealth management, as well as offering a full examination of the available securities and financial products, including alternative investments and self-managed investments. It also reviews the more proactive alternatives of starting a business or becoming a business angel.
Keywords: "Finance, personal"